Strategy, economic organization, and the knowledge economy : the coordination of firms and resources - Foss, Nicolai J. (Oxford ; New York : Oxford University Press, 2005)
"This book encompasses nine chapters which critically examine current thinking on strategy, and organization. The reasoning is non-technical. While primarily aimed at a Management Studies audience, Economists and other social scientists will also benefit from it, including Advanced Students, Academics, and Researchers."--Jacket.
Includes bibliographical references (p. [241]-276) and index.
rpm 07/09/16
Loans
Keywords: Industrial organization (Economic theory); Strategic planning; Knowledge management; Industrial organization (Economic theory)